Effects of mixed carbon sources on galactose and mannose content of exopolysaccharides and related enzyme activities in Ganoderma lucidum. Issue 45 (19th April 2016) - Peng, Lin; Li, Jie; Liu, Ying; Xu, Zhenghong; Wu, Jian-Yong; Ding, Zhongyang; Gu, Zhenghua; Zhang, Liang; Shi, Guiyang
Abstract : After calculating correlation coefficients, PGM activity regulates the mole percentage of galactose, and activities of PGI, PMI and GMP regulate the mole percentage of mannose in Ganoderma lucidum EPS synthesis. Abstract : This work investigated the effects of mixed carbon sources on the monosaccharide composition of exopolysaccharides (EPS) and activity of related enzymes, phosphoglucose isomerase (PGI), α-phosphoglucomutase (PGM), phosphomannose isomerase (PMI) and GDP-d -Man pyrophosphorylase (GMP), in the EPS biosynthesis by Ganoderma lucidum . Combinations of two carbon sources, glucose (Glc) + mannose (Man) and Glc + galactose (Gal), were applied at various mass ratios in the liquid culture of G . lucidum . The results showed that Glc, Gal, and Man were the major monosaccharides in G. lucidum EPS, and the combined mole percentages of monosaccharides were >80%, the same as those in the carbon source mixture. Activities of PGI, PMI, and GMP were correlated with Man mole percentage in EPSs and were enhanced by increasing the proportion of Gal for the carbon source Glc + Gal. PGM activity was correlated with Gal mole percentage and was reduced by increasing the Man proportion for Glc + Man. The expression of four genes encoding PGI, PMI, GMP and PGM reached peak levels on day 6 of culture, whereas the enzyme activities increased steadily from day 3 to 8. The monosaccharide composition of G . lucidum EPS for various mixed carbon source conditions thus appeared to be controlled by the translational level of genes encoding PGM, PGI, PMI, and GMP. These findings will be helpful to control the monosaccharide composition for desired biological activity of EPS produced by G . lucidum fermentation.